Nutritional Value and Consumer Acceptance of Baked Brownies fortified Snakefish (Channa striata) Protein Concentrate - Siti Kholijah; Mirna Ilza; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was aimed to determine the effect of fortifying snakefish (Channa striata) protein concentrate in baked brownies on nutritional value and consumer acceptance with different concentrations. The research was conducted in two stages: 1) ​​the production of snakefish protein concentrate, 2) the production of baked brownies with addition of snakefish protein concentrate. The method used in this research was an experimental method, using a completely randomized design (CRD) non factorial. Based on consumer acceptance the results showed that the baked brownies fortified 25% of snakefish protein concentrate (B3 treatment) was the best treatment. Based on proximate analysis that the lowest water content (14.14%) also in the baked brownies fortified 25% of snakefish protein concentrate, while the highest water content (23.54%) was without addition of snakefish protein concentrate (B0 treatment); the highest protein content (22.46%) was in B3 treatment and the lowet protein content (7.22%) in B0 treatment; the highest fat content (17.11%) was in baked brownies fortified 20% of snakefish protein concentrate (B2 treatment), while the lowest (15.67%) was in B0 treatment. Keywords: Consumer acceptance, baked brownies, protein concentrate, Channa striata.